Trends and disparities in ischemic stroke mortality and location of death in the United States: A comprehensive analysis from 1999–2020 - Jason K. Lim; Jenlu Pagnotta; Richard Lee; Do H. Lim; Jeffrey M. Breton; Zachary A. Abecassis; Raymond M. Meyer; Jeffrey C. Mai; Michael R. Levitt (PLoS ONE, 2025)
Background Stroke remains the fifth leading cause of mortality in the United States, with significant geographical and racial disparities in outcomes. Understanding trends in location of death for ischemic stroke patients is crucial for improving end-of-life care and addressing healthcare inequities. Methods & Findings This retrospective study used Centers for Disease Control and Prevention’s Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) data to examine ischemic stroke mortality, stratified by urbanization level and race. Age-adjusted mortality rates were calculated using the 2000 US standard population. Age-adjusted ischemic stroke mortality rates increased across all urbanization levels since 2009, with the most pronounced rises in non-metropolitan areas. An increasing proportion of deaths occurred at home, shifting from inpatient medical facilities. Significant disparities were observed in access to specialized end-of-life stroke care, particularly for racial minorities and rural residents. Black/African American individuals and those in rural settings were more likely to die in less specialized environments due to healthcare access barriers. Conclusions The findings highlight a critical shift in the patterns of mortality and end-of-life care preferences among ischemic stroke patients over the past two decades. These findings highlight significant shifts in the patterns of mortality and location of death among ischemic stroke patients over the past two decades, with notable differences across urbanization levels and racial groups. The increasing proportion of home deaths and persistent disparities in location of death suggest a need for further research to understand the underlying factors driving these trends and their implications for end-of-life care quality and access.